Kesetaraan Hanyu Shuiping Kaoshi Level I-IV dengan Common European Framework of Reference pada Keterampilan Menulis Bahasa Mandarin - Wikarti, Aprilia Ruby (Program Studi Pendidikan Bahasa Mandarin, Fakultas Bahasa dan Seni, Universitas Negeri Jakarta, 2022)
Abstact The development of technological disruption in the industrial revolution 4.0 makes communication in various contexts of social life increasingly across regional borders. Mandarin learning is required to have a standard level of mastery as a reference for measuring proficiency. In Europe, known as the CEFR ​​(Common European Framework for Reference for Languages), CEFR has become a common European reference frame for learning foreign languages. Unlike Europe, China government has set its own standard for Chinese languages skills, namely HSK (Hanyu Shuiping Kaoshi) This research discuss the equality between HSK writing skills level I-IV with CEFR based on the analysis result of the questions and teaching material in the “Preparation Guide for HSK level I-IV” and HSK mock test. Based on the results, it was found that teaching materials themes are equivalent with CEFR A1-B2. However, the questions items and the exercises difficulty level in